Optimization of Ethyl Carbamate Derivatization for Spectrophotometric and Electrochemical Detection - Klikarová, Jitka; Sýs, Milan; Šantrůčková, Veronika; Toušková, Monika (BEST Servis, 2023)
Ethyl carbamate is a process contaminant posing a potential hazard to human health. It is formed in food and beverages mainly during their fermentation and it is primarily contained in stone fruit spirits. Prior to analysis, derivatization of ethyl carbamate is required since it lacks a chromophore, fluorophore, or electrophore in its structure, making direct detection challenging or non-selective. Hence, this research deals with the possibilities of ethyl carbamate derivatization for its subsequent spectrophotometric or electrochemical detection. The aim of the work was to develop a rapid, simple, cheap, and manually undemanding approach for ethyl carbamate determination, allowing its preliminary screening in food samples of various types.
Optimalizace derivatizace ethylkarbamátu pro spektrofotometrickou a elektrochemickou detekci
Keywords: Ethyl Carbamate; Derivatization; Spectrophotometric Detection; Electrochemical Behaviour; Etylkarbamát; derivatizace; spektrofotometrická detekce; elektrochemické chování